Pengaruh Dimensi E-WOM Terhadap Revisit Intention Melalui Destination Image Sebagai Variabel Mediasi Wisatawan Kebun Binatang Bandung - Amelia Khoirun Nissa; Abdul Ahmad Hafidh Nurmansyah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of E-WOM dimensions on revisit intention through destination image as a mediating variable for tourists visiting Bandung Zoo. The study population consists of male and female tourists who have read about Bandung Zoo through the internet, using purposive sampling to collect samples. Respondents are tourists aged at least 17 years who have visited Bandung Zoo at least once in the last two years. The sample size used in this study was 100 respondents. Data was collected through Google Forms based on a Likert scale, and multiple linear regression analysis was conducted using SPSS version 26 and the Sobel test. The results of the study indicate that the E-WOM dimension has a positive influence on destination image. The E-WOM dimension has a positive influence on revisit intention. Furthermore, destination image has a positive influence on revisit intention. Destination image is able to mediate the influence of E-WOM quality and E-WOM quantity on revisit intention. Therefore, the management of Bandung Zoo can prioritize improving all indicators that form E-WOM and destination image, as this is expected to have a positive impact on revisit intention.